Rational Design of Liquid-Liquid Microdispersion Droplet Microreactors for the Controllable Synthesis of Highly Uniform and Monodispersed Dextran Microspheres - Ma, Li (Langmuir : the ACS journal of surfaces and colloids, 2024)
Hydrogel microspheres are biocompatible materials widely used in biological and medical fields. Emulsification and stirring are the commonly used methods to prepare hydrogels. However, the size distribution is considerably wide, the monodispersity and the mechanical intensity are poor, and the stable operation conditions are comparatively narrow to meet some sophisticated applications. In this paper, a T-shaped stepwise microchannel combined with a simple side microchannel structure is developed to explore the liquid-liquid dispersion mechanism, interfacial evolution behavior, satellite droplet formation mechanism and separation, and the eventual successful synthesis of dextran hydrogel microspheres. The effect of the operation parameters on droplet and microsphere size is comprehensively studied. The flow pattern and the stable operation condition range are given, and mathematical prediction models are developed under three different flow regimes for droplet size prediction. Based on the stable operating conditions, a microdroplet-based method combined with UV light curing is developed to synthesize the dextran hydrogel microsphere. The highly uniform and monodispersed dextran microspheres with good mechanical intensity are synthesized in the developed microfluidic platform. The size of the microsphere could be tuned from 50 to 300 μm with a capillary number in the range of 0.006-0.742. This work not only provides a facile method for functional polymeric microsphere preparation but also offers important design guidelines for the development of a robust microreactor